Application of hydroponic technology and processing variations to enhance food security and prevent stunting - Nani Yulianti; Dhika Prita Hapsari; Rosy Hutami; Dodi Dodi; Trisna Setiadi; Depanito Ismail; Yuyun Puspitasari; Nirma Ruhil Hadi Putra (University of Merdeka Malang, 2024)
Hydroponics is a modern plant cultivation system without soil to produce clean, healthy, and fresh vegetables. The availability of fresh, healthy food is a key factor in preventing stunting. This community service activity aims to increase food security and prevent stunting through vegetable cultivation using hydroponic technology. Methods used include socialization, training, practice, mentoring, monitoring, and evaluation of hydroponic technology and its processing. Results show that partners experienced increased empowerment, with knowledge of hydroponics and its processing improving by >30 percent. Partner skills in producing hydroponic vegetable products significantly improved, transitioning from no prior experience to being skilled at hydroponic cultivation, with increased production. This activity also yielded various vegetables (water spinach, spinach, bok choy, and Chinese kale) grown using hydroponic systems. Additionally, DFT hydroponic system facilities with a capacity of 200 plants per installation (4 installations) and processing tools were provided, enabling the community to access fresh, nutritious food and support stunting prevention.